Pulmonary Rehabilitation in Guillain-Barré Syndrome (GBS) - Andi Dala Intan; Anita Ratnawati (Indonesian Journal of Physical Medicine & Rehabilitation, 2015)
GBS was first described by Landry in 1859, a post-infectious polyneuropathy primarily not only affecting the motor system, but also on the sensory nervous system and the autonomic nervous system. It is acute and known as an autoimmune disease. The disease is more common in male, 1.5 times higher than women in western countries, affects any ages, mostly adults. 60% of GBS patients will be preceded by an upper respiratory tract disease and 27% unidentified illness that preceded it. Started with lower limb weakness and progresses to the upper limb and eventually the bulbar muscles; known as Landry’s Ascending Paralysis or rubbery legs. The diagnosis can be confirmed by history and physical examination. The prognosis depends on the subtype of GBS. For about 85% of patients will have functional recovery within a few months to a year. Rehabilitation in GBS management generally emphasis on immobilization and management of pneumonia and respiratory failure. GBS patients with respiratory dysfunction should get immediate rehabilitation and obtain a specific treatment program.Keywords: Guillain Barre Syndrome,Respirasi Rehabilitation,Breathing Exercise, Inspiratory muscle training